Sistem Penguburan Masyarakat Desa Pao Kabupaten Gowa - Syandri Syandri; Akhmad Hanafi Dain Yunta (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2020)
Pao Village is one of the villages where STIBA Makassar Community Service Program (KKN) students were placed, in Bantimurung District. The purpose of this study was to elaborate burial system of caste in Pao community. Data collection in this study was through interviews with several community leaders in Pao village. The strategy employed was to give assignments to all KKN students and gather information that was found, then describe the findings in the form of a written article. The results show that the people of Pao Village are of caste level, those are: 1) Puang, 2) Karaeng, 3) Daeng, and 4) Ata (servant). Each of these levels has its own burial location and may not be mixed with the others because they are considered to have differences in social status while they live.